2018
DOI: 10.1038/s41598-018-24150-3
|View full text |Cite
|
Sign up to set email alerts
|

Possible superconductivity in the Bismuth IV solid phase under pressure

Abstract: The first successful theory of superconductivity was the one proposed by Bardeen, Cooper and Schrieffer in 1957. This breakthrough fostered a remarkable growth of the field that propitiated progress and questionings, generating alternative theories to explain specific phenomena. For example, it has been argued that Bismuth, being a semimetal with a low number of carriers, does not comply with the basic hypotheses underlying BCS and therefore a different approach should be considered. Nevertheless, in 2016 base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…This, together with the overflow of electrons from the d shell to the sp shells may be an indicator of an unexpected behaviour. However, since identifying unambiguously the cutoff value to calculate the nn in amorphous metals is a controversial subject [10] we opted for a complementary, direct approach in a manner similar to our previous calculations on bismuth [16,17], and obtained the densities of electronic states with α spins and with β spins to see if they indicate a net magnetic moment, and they do, Fig. 4(a).…”
Section: Methodsmentioning
confidence: 99%
“…This, together with the overflow of electrons from the d shell to the sp shells may be an indicator of an unexpected behaviour. However, since identifying unambiguously the cutoff value to calculate the nn in amorphous metals is a controversial subject [10] we opted for a complementary, direct approach in a manner similar to our previous calculations on bismuth [16,17], and obtained the densities of electronic states with α spins and with β spins to see if they indicate a net magnetic moment, and they do, Fig. 4(a).…”
Section: Methodsmentioning
confidence: 99%
“…A year after our prediction, experimentalists proved us correct and they found that the Wyckoff structure superconducts below 0.53 mK at ambient pressure [9]. We had ventured to estimate superconducting temperatures for bismuth under various conditions; for the crystalline phase, that had not been found to superconduct, we succeeded; our other predictions await verification [7,10]. So, with this succinct background we decided that bismuth was the ideal "guinea pig" to test the effect of negative pressures and we undertook the search to see if it could become metallic or a semiconductor under expansion, and what the possibilities were to find it in a superconducting state.…”
Section: Introductionmentioning
confidence: 68%
“…Bismuth was first found to be a superconductor when in the amorphous phase at ambient pressure [4,5]. Then, when the Wyckoff crystalline phase (the structure at room temperature and atmospheric pressure) was subjected to positive pressures it changed crystalline structures but maintained the superconducting properties for most of the new topologies (See [6] and [7], and references contained therein). Then we came into the play and predicted, using a simple BCS approach, that although the crystalline Wyckoff structure had not been found to superconduct, it should, for temperatures below 1.3 mK [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mostly fine-grained aggregates of a single mineral or mixture of several sulphides, sulphosalts and/or native metals and their alloys (Cu, Pb, Zn, Cd, Bi, Ag, Sb, As, Te) are subsolidus in origin. Anhedral to subhedral grains, and aggregates of rather common native bismuth with the melting point about 260-270 °C (e.g., Živkovič and Živkovič 1996;Valladares et al 2018) is mostly among the earliest phases in these assemblages, and it suggests that sulphides crystallized at evidently lower T typically ~200-100 °C (e.g., Černý and Harris 1978;Márquez-Zavalía et al 2012). In contrast, crystallization of stannitegroup minerals, typical sulphides in granitic pegmatites (Kissin et al 1978;Černý et al 2001), proceeded at higher T ~400 °C.…”
Section: Conditions Of Origin Of Sulphide Mineralizationmentioning
confidence: 99%
“…Argentopentlandite, pentlandite and parkerite occur only on a microscopic scale as irregular aggregates and inclusions in major and minor sulphides. The temperature of the crystallization of sulphides is constrained by the textural relations and mineral assemblage: polysynthetic twinning of chalcopyrite suggests the transformation of high-temperature cubic chalcopyrite to tetragonal one at T = 550 °C (Kostov and Stefanova 1981;Čvileva et al 1988); sphalerite stars in chalcopyrite indicate T ~500-400 °C (Kostov and Stefanova 1981;Sugaki et al 1987), argentopentlandite has the upper limit of T < 455 o C (Mandziuk and Scott 1977), marcasite has the upper-temperature stability limit at T = ~240 °C (Murowchick 1992), and native bismuth as the late mineral suggests T < ~270 °C (melting point 271 °C, Živkovič and Živkovič 1996; T = 267 to 250 ºC at P = 1 to 5 kbar, Valladares et al 2018). Early sulphides (pyrrhotite, chalcopyrite, sphalerite, argentopentlandite) crystallized at T < ~400-450 °C, whereas pyrite, marcasite, galena, parkerite, and native Bi at T < 240 °C.…”
Section: Conditions Of Origin Of Sulphide Mineralizationmentioning
confidence: 99%